(untitled) (IITM Journal of Business Studies, 2024)
Vom Brocke, Jan, Rosemann, Michael (Eds.), Business Process Management 1: Introduction, Methods, and Information Systems (Second Edition), 2015, Springer-Verlag Berlin Heidelberg, pp 727, 229, ISBN 13- 978-3-642-45099-0, DOI 10.1007/978-3-642-45100-3. This bestselling book by Jan vom Brocke and Michael Rosemann’s on ‘Business Process Management 1: Introduction, Methods, and Information Systems (Second Edition) as a first volume focuses on defining BPM approaches and examining various BPM methods and process-aware information systems. The book vividly guides in the integration of BPM into corporate methodologies and information systems for a customer centred approach to organisation management. This book’s intended audience is both academic and non-academic readership.